Exome Sequence Analysis of 14 Families With High Myopia - Kloss, Bethany A. (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: To identify causal gene mutations in 14 families with autosomal dominant (AD) high myopia using exome sequencing. METHODS: Select individuals from 14 large Caucasian families with high myopia were exome sequenced. Gene variants were filtered to identify potential pathogenic changes. Sanger sequencing was used to confirm variants in original DNA, and to test for disease cosegregation in additional family members. Candidate genes and chromosomal loci previously associated with myopic refractive error and its endophenotypes were comprehensively screened. RESULTS: In 14 high myopia families, we identified 73 rare and 31 novel gene variants as candidates for pathogenicity. In seven of these families, two of the novel and eight of the rare variants were within known myopia loci. A total of 104 heterozygous nonsynonymous rare variants in 104 genes were identified in 10 out of 14 probands. Each variant cosegregated with affection status. No rare variants were identified in genes known to cause myopia or in genes closest to published genome-wide association study association signals for refractive error or its endophenotypes. CONCLUSIONS: Whole exome sequencing was performed to determine gene variants implicated in the pathogenesis of AD high myopia. This study provides new genes for consideration in the pathogenesis of high myopia, and may aid in the development of genetic profiling of those at greatest risk for attendant ocular morbidities of this disorder.